Morphological and molecular identification of an unknown fungal isolate from Al‐Dujail District: A new record of Tulostoma winterhoffii in Iraq - Taghreed Khudhur Mohammed; Hanaa Naji Abdullah; Sinai Waleed Mohammed; Muntadher Fadhil Jassim (Universitas Gadjah Mada, 2025)
The Tulostoma genus, known as stalkballs or stalked puffballs, belongs to the Agaricaceae family. This study was designed to identify an unknown fungal species collected from the Al‐Dujail district in Iraq based on morphological examination and molecular analysis of the internal transcribed spacer (ITS) region. Between April and July 2019, samples were collected from garden soil in the Al‐Dujail district, Salah Al‐Din Governorate, Iraq. Morphological characteristics were documented using light microscopy. Genomic DNA was extracted and purified, and the ITS region was amplified using conventional PCR with specific primers. The amplified products were sequenced, and phylogenetic analysis was conducted using MEGA11 software. Morphological analysis revealed smooth, yellow to brown, nearly circular basidiospores. The ITS region amplification yielded a 588 bp fragment. Basic Local Alignment Search Tool (BLAST) analysis showed 91% similarity between the sample (S1‐ITS‐Iraq) and Tulostoma winterhoffii (accession number KU518975.1). The isolate was assigned in GenBank under accession number PV249065, with phylogenetic analysis positioning S1‐ITS‐Iraq in a cluster with the Tulostoma species, with a bootstrap value of 97%, indicating a close relationship. The fungal sample from Iraq was identified as a new record within the genus Tulostoma, marking the first report of T. winterhoffii in the region.